2021
DOI: 10.7717/peerj.12143
|View full text |Cite
|
Sign up to set email alerts
|

Construction of competing endogenous RNA interaction network as prognostic markers in metastatic melanoma

Abstract: Malignant melanoma (MM) is a malignant tumor originating from melanocytes, with high aggressiveness, high metastasis and extremely poor prognosis. MM accounts for 4% of skin cancers and 80% of mortality, and the median survival of patients with metastatic melanoma is only about 6 months, with a five-year survival rate of less than 10%. In recent years, the incidence of melanoma has gradually increased and has become one of the serious diseases that endanger human health. Competitive endogenous RNA (ceRNA) is t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…More recently, He et al reported that microRNA-3662 (miR-3662) downregulates its target mRNAs and is associated with suppression of melanoma cell proliferation. LncRNAs negatively interact with miR-3662 and interfere with miR-3662 function, thus promoting proliferation [ 43 ].…”
Section: Melanomamentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, He et al reported that microRNA-3662 (miR-3662) downregulates its target mRNAs and is associated with suppression of melanoma cell proliferation. LncRNAs negatively interact with miR-3662 and interfere with miR-3662 function, thus promoting proliferation [ 43 ].…”
Section: Melanomamentioning
confidence: 99%
“…Surgical excision is generally the standar treatment for low risk lesions. However, Mohs micrographic surgery is used for cSC lesions on the head, neck, and other anatomically and cosmetically sensitive areas, and has been reported to have better cure rates than a standard excision [43]. The 5-year su vival rate for SCC is 99% when detected early.…”
Section: Squamous Cell Carcinomamentioning
confidence: 99%